Kedudukan As-sunnah Sebagai Sumber dan Hukum Pendidikan Islam di Era Milenial - Muhammad Ali; Antiya Safira Prajayanti (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2019)
As-Sunnah has meanings derived from language, terms, and according to the scholars. Al-Sunnah has a role as a source in Islamic teachings to be an explanation of the contents of the content of the Qur'an, because the Qur'an requires a deeper explanation and the Prophet very much expects his people to follow his teachings. Islam which is based on Al-Qur'an and Al-Hadith which makes guidelines for Muslims have benefits not only regulates in terms of worship, but also directs the ummah in giving demands on various work-related problems. The inkar as-sunnah movement in Indonesia to make progress that caused Muslim upheaval to the daily pages of newspapers and magazines. There are also those who argue that adultery is bid'ah, and bid'ah has two meanings, namely mazmummah and mahmudah.